(untitled) (Scientific journal of the Fergana State University, 2024)
It’s no secret that modern demands require our youth to learn many languages. To do this, our youth definitely turn to language learning resources. This article talks about how to easily learn Korean on your own without separating it from study and work, the problems that arise during learning and how to overcome them. It is worth noting that the article is important for all students of Korean and foreign languages, as a necessary tool.